If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -29 + 12x = 29 + 9x Solving -29 + 12x = 29 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. -29 + 12x + -9x = 29 + 9x + -9x Combine like terms: 12x + -9x = 3x -29 + 3x = 29 + 9x + -9x Combine like terms: 9x + -9x = 0 -29 + 3x = 29 + 0 -29 + 3x = 29 Add '29' to each side of the equation. -29 + 29 + 3x = 29 + 29 Combine like terms: -29 + 29 = 0 0 + 3x = 29 + 29 3x = 29 + 29 Combine like terms: 29 + 29 = 58 3x = 58 Divide each side by '3'. x = 19.33333333 Simplifying x = 19.33333333
| 28562=x | | -12+(-4+9)= | | 3(t+7)=7t-3 | | (x^2+7x+10)(x^2+7x+10)(x^2+7x+10)=0 | | -x=-y+2 | | 18=2(3k+1)-4 | | 4x+48=12x | | x^2+10=154 | | 2.5x+6=60 | | 2y^2+3y-35= | | 8y=33-5y | | 9d-9=18 | | 9u=4u+35 | | 6m+4m-m+5=23 | | 6(x+3)-20=32 | | 3x-5x+1=8-2x | | 2x+3+0.75= | | 9y^2+18y+8= | | x^2-16x-132=0 | | 10=30(20)+b | | y=ln(x+2)-4 | | 10(x-2)+12(x+4)=x | | 9x-37=12x+23 | | -7y-2x=-13 | | 5.5x+1.2-0.3=7.2x-3 | | 13=4x?9 | | 12+x^2=8y-y^2 | | -2[3+4(x-1)]=x | | x+2x+3x=306 | | -3-66x=9 | | 5.2x=3x | | 1=2(12) |